Rehabilitation or Retribution? A Socio-Legal Comparison of Criminal Sanctions and Social Reintegration in Indonesia and Spain - Arifin, Ridwan; Cassandro, Izan Mateo (The Indonesian Journal of Socio-Legal Studies, 2026)
This study examines the legal, institutional, and socio-cultural mechanisms influencing the social reintegration of ex-offenders in Indonesia and Spain. Despite a global trend toward rehabilitative approaches, practical implementation reveals significant divergence due to structural, cultural, and economic factors. Indonesia’s penal system, guided by Law No. 22 of 2022 and the new Criminal Code (KUHP), emphasizes statutory rehabilitation and vocational and spiritual programs. However, challenges such as prison overcrowding, limited post-release support, and societal stigma constrain effectiveness. Judicial decisions indicate cautious application of restorative provisions, reflecting both public expectations and institutional limitations. In Spain, rehabilitation is constitutionally entrenched under Article 25(2) of the Constitution and operationalized through the General Penitentiary Organic Law (Ley Orgánica General Penitenciaria; LOGP), which mandates individualized treatment, progressive custody, and open-regime programs. Court rulings reinforce the rights of inmates and ex-offenders to social reintegration, while structured vocational, psychological, and community programs enhance post-release outcomes. Socio-legal analysis shows that Indonesia’s reintegration is vulnerable to societal exclusion, whereas Spain demonstrates effective alignment between law, institutional capacity, and cultural legitimacy. The study integrates theoretical frameworks such as labelling theory, desistance theory, and reintegrative shaming to explain the interplay between law, institutions, and social contexts. Findings indicate that successful social reintegration requires coordinated legal, institutional, and societal mechanisms, with attention to economic inclusion and cultural acceptance.